Last night at the telegraph club eaudiobook - Lo, Malinda (Listening Library, 2021)
Acclaimed author of  Ash  Malinda Lo returns with her most personal and ambitious novel yet, a gripping story of love and duty set in San Francisco's Chinatown during the 1950s. "That book. It was about two women, and they fell in love with each other." And then Lily asked the question that had taken root in her, that was even now unfurling its leaves and demanding to be shown the sun: "Have you ever heard of such a thing?" Seventeen-year-old Lily Hu can't remember exactly when the question took root, but the answer was in full bloom the moment she and Kathleen Miller walked under the flashing neon sign of a lesbian bar called the Telegraph Club.  America in 1954 is not a safe place for two girls to fall in love, especially not in Chinatown. Red-Scare paranoia threatens everyone, including Chinese Americans like Lily. With deportation looming over her father—despite his hard-won citizenship—Lily and Kath risk everything to let their love see the light of day. *This audiobook includes a PDF of the bibliography and acknowledgments from the book.